Hydraulic jump on rough beds: conceptual modeling and experimental validation - Umut Türker; Manousos Valyrakis (Water Supply, 2021)
The aim of this study was to assess and quantify the effect of channel bed roughness on hydraulic jumps based on sound physical theories. Assuming that integrated bed shear stress due to surface roughness changes linearly with supercritical velocity, a novel definition for the shear force coefficient and for roller length were obtained. Experimental findings and Pearson's correlation verify that the developed equations perform reasonably well and they prove that a linear correlation assumption between integrated bed shear stress and supercritical velocity is valid for a Froude number between 1.1 and 9.8. The shear force coefficient is defined in terms of the Reynolds coefficient and the supercritical flow velocity is directly related to the modified Reynolds number. A new analytical equation for roller length as a function of the modified Reynolds number was also developed and validated by using data from the experimental study. HIGHLIGHTS The tendency of the Reynolds coefficient to approach a fixed value increases as the modified Reynolds number increases.; The results of this study showed that the modified Reynolds number is important in roller length analysis and cannot be ignored.; Pearson's correlation analysis showed a significant positive linear correlation between integrated bed shear stress and upstream supercritical velocity.;